The Role of Footwear in the Pathogenesis of Hallux Valgus: A Proof-of-Concept Finite Element Analysis in Recent Humans and Homo naledi - Yu, Genyu; Fan, Yuzhou; Fan, Yuxuan; Li, Ruining; Liu, Yaming; Antonijevic, Djordje; Milovanovic, Petar; Zhang, Bo; Li, Zhiyu; Djuric, Marija; Fan, Yifang (Frontiers in Bioengineering and Biotechnology, 2020)
Hallux valgus (HV), the bunion of the first metatarsophalangeal joint (MTPJ), bothers many adults. No consensus has been reached about the causes of HV, be it a hereditary, or acquired, or multifactorial disease. Nor has agreement been reached using MTPJ angle to assess HV based on X-ray because in most cases the assessment of MTPJ is not reliable as it depends on the posture during scanning. In this study, we assume that HV is predominately acquired and that shoe wearing per se is an important player in HV pathogenesis. To verify our hypothesis, a CT-based finite element (FE) model of the first MTPJ of fossil remains of bear-footed Homo naledi was created and compared to that of five contemporary shoe-wearing wrestlers (10 models from two scans at an interval of about 18 months) because Homo naledi’s first MTPJ is an ideal model for non-shoe wearing with parallel sesamoid grooves. We developed the first MTPJ structure transformation method and created MTPJ joint capsule model for both Homo naledi and wrestlers. Constraint on the medial side of the first MTPJ capsule was set to simulate shoe-wearing conditions compared to the lack of medial constraint for barefooted conditions. Analysis of eight FE models of different angles for the first MTPJ of Homo naledi was performed by the first MTPJ transformation method and results showed that stress concentrated on the medial capsule of the first MTPJ in simulated shoe-wearing conditions, even at MTPJ angle of 0°. Increase in the first MTPJ angle further increased stress concentration on the medial side, and stress-growth relationship might reveal the causes of HV. We further developed a method to position the first MTPJ in wrestlers and created CT-based models at two time points. It was evident that the first MTPJ angle increased in all but one athlete, with a maximal increase of 4.03 degrees. This verifies our hypothesis that HV might be developed by wearing shoes. Further longitudinal studies with larger sample sizes are needed to additionally validate our results and determine the magnitude of the effects of shoe wearing on development and progression of HV.